Carbon Footprint of Cold Chain System and a Case Analysis - Liu Guanghai; Wu Junzhang; You Li; Xie Ruhe; Tang Haiyang; Zhong Junfeng; Qu Ruigui (Zhileng xuebao)
In order to measure the carbon emissions of cold-chain logistics systems, a systematic method for calculating the carbon footprint of cold-chain logistics was proposed and a carbon footprint model for cold chain logistics system was constructed in this study. An empirical analysis of the carbon footprint of cold chain logistics was carried out throughout the course of bananas. The life-cycle assessment, input-output, and carbon emission coefficient methods were used to define the scope of the carbon footprint accounting for different circulation links of cold chain logistics, and the produce and harvest processing were measured. Carbon emissions from various links such as precooling and refrigerated transportation, storage, distribution operations, and terminal sales are calculated. Under the condition of setting parameters, the total system cost is 3.5474 million yuan, and the total amount of carbon emissions is 148.62 tons; when the total cost of the system is 3.6921 million yuan, the corresponding total system carbon emissions are 145.21 tons. After a sensitivity analysis of the carbon footprint of the cold chain logistics, the increase in the carbon tax can increase the total cost of the system by a maximum of 0.8%, while an increase in the corruption rate can increase the total system cost and carbon footprint by nearly 35% in the same trend. The research shows that this model can effectively measure the carbon footprint in cold chain logistics activities.